Gender Wayang Learning Video Design to Build the Characters of The Millennial Generation - Lia Susanthi, Nyoman; Suratni, Ni Wy.; Arya Satyani, Ida Ayu Wayan; Hery Budiyana, Ketut; Dwiyani, Ni Kadek; Indira, Wahyu (Institut Seni Indonesia Denpasar, 2023)
Nowadays the number of students engaged in criminal acts is alarming. In response to this, the role of parents, teachers in schools and the government is very important to strengthen character building, especially in the golden generation, namely students. Strengthening character education should not only be pursued through formal schools but also through non-formal and informal routes. Art studios can be a platform that offers an alternative to character building. However, in the process of transferring knowledge in the studio, several problems are encountered, including the low increase in students' ability to learn gender (Balinese musical instrument). For this reason, the gender wayang learning video was designed by implementing character education values for the millennial generation. The design of the gender wayang learning video to help build the character of the millennial generation uses a qualitative descriptive method. The data collection method was carried out through literature studies and field studies by interviewing the director and the production team involved in creating the learning video. In addition, an observation was made at one of the studios in Bali which has quite a lot of students, namely the Swati Swara Studio. The design and creation of a gender wayang learning video for the millennial generation began with conducting a target analysis for the millennial generation. Sanggar Swasti Swara is a place where one can find millennials who need a form of teaching using technology. For this reason, gender wayang learning video is the solution for this generation. This learning video is designed to be easy to access, namely having a good quality video that can be sent via cellphone and stored on the YouTube channel so that they are easy to access and distribute. The millennial generation at Sanggar Swasti Swara, in terms of learning style, prefers learning from practice, visuals, and a learning process that can be applied at home in groups and is fun. In addition, the educational values of the nation's character can be included in the text of the gender wayang learning video, namely religious values, tolerance, hard work, and love for the motherland.